(untitled) (Samota Journal of Biological Sciences, 2024)
Bactrocera is a pest that damages horticultural crops and often thwarts farmers’ harvests, especially fruit and vegetable crops. This study aims to determine the Types of Bactrocera in Crystal Guava Plants (Psidium guajava) in North Perendekan Hamlet, Giri Sasak Village, Kuripan District, West Lombok Regency This type of research is descriptive and exploratory. The sampling technique used is a purposive sampling technique to determine the sampling point. The results of this study are the types of Bactrocera found in North Perendekan Hamlet, Giri Sasak Village, which are from the types of Bactrocera Papayae and Bactrocera Umbrosa. The type of Bactrocera Papayae found in 684 has a medium-sized shape, almost the entire head is brownish-yellow, the costal wings are not shaped like a belly fishing rod. Meanwhile, the shape of Bactrocera umbrosa that was found to have black spots on the face and was medium in size and round in shape. The wing part is easily recognizable by the image of three transverse bands. The allies are black with yellow stripes on both sides laterally. abundance found in Bactrocera umbrosa which only amounts to 28 imago in the crystal guava plant. From the results of this study, it can be concluded that the Bactrocera intake obtained by doing the 1st, 2nd, and 3rd repetitions at 5 different points, namely in the first intake the number of Bactrocera obtained at 5 different points was 113 Bactrocera, in the 2nd repetition as many as 407 Bactrocera, while in the 3rd repetition Bactrocera was obtained as many as 192. Population density, Bactrocera papayae has the highest population density with an average population of 684 imago. Meanwhile, the population density found in Bactrocera umbrosa is only 28 imago in crystal guava plants. Keywords: Bactrocera, Identification, Bactrocera Papayae, Bactrocera Umbrosa, Crystal Guava